Minimally Invasive Distal Metatarsal Osteotomy for Mild-to-Moderate Hallux Valgus Deformity - Yu-Chuan Lin (Kaohsiung Journal of Medical Sciences, 2009)
Minimally invasive surgery has recently been introduced for foot and ankle surgery, and hallux valgus surgery is no exception. The purpose of our study was to analyze the early results and to present our experience of minimally invasive distal metatarsal osteotomy in correcting mild-to-moderate hallux valgus deformities. Between September 2005 and December 2006, 31 consecutive patients (47 feet) with mild-to-moderate hallux valgus deformities underwent minimally invasive distal metatarsal osteotomies. The clinical and radiographic outcomes were assessed. The satisfaction rate was 90.32%. The mean total American Orthopedic Foot and Ankle Society halluxmetatarsophalangeal-interphalangeal scale was 92.7 points. Complications included two (4.26%) episodes of stiffness, six (12.77%) episodes of pin tract infection, and one (2.13%) deep infection. There were no cases with nonunion, malunion, overcorrection, transfer metatarsalgia or osteonecrosis. On weight-bearing anteroposterior foot radiographs, the mean hallux valgus angle and first intermetatarsal angle corrections were 11.8° and 6.3°, respectively, which is a statistically significant difference (p < 0.001) between the preoperative and postoperative status. Here, minimally invasive distal metatarsal osteotomy was associated with good satisfaction, functional improvement and low complication rates. This technique offers an effective, safe and simple way to treat hallux valgus with a first intermetatarsal angle less than 15°.